Nadetnična identiteta kot točka prešitja multietničnih družb - Godina, Vesna V. (Teorija in praksa, 2009)
In my text I discuss a supra-ethnic identity as a point de capiton of multiethnic societies. My hypothesis is that a supra-ethnical identity as a point de capiton plays a fundamental political role in the social and political integration of multiethnic societies. I present a basic theoretical model which shows how a supra-ethnic identity integrates different ethnic groups in a multiethnic society into a "supra-ethnic group", which is the political subject in multiethnic societies. Some aspects of the relationship between ethnic identities and a supra-ethnic identity will be discussed to show how individuals in such situations synchronise their ethnic and supra-ethnic identities and how through such a synchronisation conflicts between different ethnic groups in a specific society can be neutralised. I use in my text empirical materials from ex-Yugoslavia.
Keywords: Etnical identity; Etnična identiteta; Multicultural society; Multikulturna družba; Jugoslavija; Yugoslavia; družba; society; večkulturnost